STRENGTH-CYCLE CURVES FOR MULTI-AXIAL FATIGUE OF POLYESTER REINFORCED BY GLASS FIBER - Kareem Radhi, Samira; Sabah Muhammed, Ehsan; Abd Al-Sahab Ali, Karar (Journal of Engineering and Sustainable Development, 2016)
This study discusses the development of a multi-axial fatigue testing machine, and studies the fatigue behavior of cantilever glass fiber composites beam under in phase bending-torsion dynamic loadings. The effect of bending–twisting deflections and the number of layers on the peak strength, fatigue life, and failure mechanisms are analyzed. Two types specimen (two dimension woven fiberglass (2D) and three dimension stitching fiberglass (3D)) are investigated. The results of both 2D and 3D show that the strength is increased significantly with increase bending-torsion stresses, while the damage becomes faster. The strength is reduced rapidly in about the first 30% of its fatigue life due to matrix cracking, which is then followed by a much slower rate of strength reduction until the failure. And the samples strength is increased as the number of layers increased by 20±3 % when tested under the same loading conditions. Furthermore the strength in 2D specimen is higher than the strength in the 3D specimen by about 20% when subjected to the same bending deflection-twisting angle. The fatigue life in 3D sample is greater than fatigue life in 2D samples by about 17% when tested under the same loading conditions.